2018
DOI: 10.1038/s41598-018-35179-9
|View full text |Cite
|
Sign up to set email alerts
|

Active Confirmation Bias in the Evaluative Processing of Food Images

Abstract: Predictive processing is fundamental to many aspects of the human mind, including perception and decision-making. It remains to be elucidated, however, in which way predictive information impacts on evaluative processing, particularly in tasks that employ bivalent stimulus sets. Various accounts, including framing, proactive interference, and cognitive control, appear to imply contradictory proposals on the relation between prediction and preference formation. To disambiguate whether predictive cues produce co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…In our previous study (Ounjai et al, 2018), analysis of the reaction times further showed that valid predictions (e.g., a positive prediction followed by an appetitive food image) produced faster evaluations than invalid predictions. Moreover, during the waiting period between the predictive cue and the target image, we observed gaze biases indicative of a preparatory process in line with the prediction.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In our previous study (Ounjai et al, 2018), analysis of the reaction times further showed that valid predictions (e.g., a positive prediction followed by an appetitive food image) produced faster evaluations than invalid predictions. Moreover, during the waiting period between the predictive cue and the target image, we observed gaze biases indicative of a preparatory process in line with the prediction.…”
Section: Introductionmentioning
confidence: 76%
“…Would we see bias in line with the prediction (higher ratings for expected treats) or an opposite effect (higher ratings for surprise treats)? In our previous study, we asked this question empirically, using an evaluation task with a bivalent set of food images (Ounjai et al, 2018). Our data showed that appetitive food images were rated higher following a positive prediction than following a negative prediction, and vice versa for aversive food images.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations